Ex-situ modification of nanostructured hydroxyapatite by colloidal CdS particles - N.S. Kozhevnikova; E.A. Bogdanova; V.M. Skachkov; I.V. Baklanova; A.P. Tyutyunnik; L.Yu. Buldakova; M.Yu. Yanchenko; A.A. Yushkov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The article discusses the possibility of obtaining functional composite materials with pronounced photocatalytic properties. A hybrid composite material based on nanoscale cadmium sulfide fixed on a matrix of hydroxyapatite obtained by precipitation from solution has been developed. The initial components and synthesized samples were certified using some modern physico-chemical analysis methods: X-ray phase analysis, energy dispersive X-ray analysis, Raman spectroscopy, scanning electron microscopy, the Brunauer-Emmett-Teller method. The functional characteristics of the developed composite material Ca10(PO4)6(OH)2-CdS, in particular, the photocatalytic activity under the action of ultraviolet or visible radiation, are investigated. The efficiency of using the developed composite material as a photocatalyst was evaluated by the rate of oxidation of p-dihydroxybenzene (hydroquinone). Based on experimental data obtained, the values of the constants of the reaction rate of photocatalytic oxidation of hydroquinone and the time of its half-conversion under various conditions (radiation, the presence of a catalyst) are calculated. It is proved that the developed composite material, which is a hydroxyapatite modified with colloidal CdS particles, has pronounced catalytic properties and is a promising material for use as a photocatalyst. A patent application has been filed for the developed composite material.